2020
DOI: 10.1073/pnas.1918994117
|View full text |Cite
|
Sign up to set email alerts
|

The versatile functions of OsALDH2B1 provide a genic basis for growth–defense trade-offs in rice

Abstract: In plants, enhanced defense often compromises growth and development, which is regarded as trade-offs between growth and defense. Here we identified a gene, OsALDH2B1, that functions as a master regulator of the growth–defense trade-off in rice. OsALDH2B1 has its primary function as an aldehyde dehydrogenase and a moonlight function as a transcriptional regulator. Loss of function of OsALDH2B1 greatly enhanced resistance to broad-spectrum pathogens, including fungal blast, bacterial leaf blight, and leaf strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 47 publications
1
56
0
Order By: Relevance
“…Our theory is further substantiated by research in rice with an overexpressed GST (OsGSTL1) possessing GPOX activity, in which transgenic plants displayed enhanced herbicide tolerance (Hu et al 2009). Moreover, some enzymes and proteins demonstrate multifunctional or "moonlighting" activities (Huberts and van der Klei 2010; Jeffery 2014; Ke et al 2020) that might also occur with certain A. tuberculatus GSTs. A multifunctional enzyme is somewhat analogous to a single gene conferring metabolic crossresistance, or pleiotropic effect, to seemingly unrelated herbicide chemistries (Beckie and Tardif 2012;Dyer 2018).…”
Section: Population Bmentioning
confidence: 71%
“…Our theory is further substantiated by research in rice with an overexpressed GST (OsGSTL1) possessing GPOX activity, in which transgenic plants displayed enhanced herbicide tolerance (Hu et al 2009). Moreover, some enzymes and proteins demonstrate multifunctional or "moonlighting" activities (Huberts and van der Klei 2010; Jeffery 2014; Ke et al 2020) that might also occur with certain A. tuberculatus GSTs. A multifunctional enzyme is somewhat analogous to a single gene conferring metabolic crossresistance, or pleiotropic effect, to seemingly unrelated herbicide chemistries (Beckie and Tardif 2012;Dyer 2018).…”
Section: Population Bmentioning
confidence: 71%
“…Prior studies have revealed that activation of JA signaling plays a positive role in Xoo resistance in rice (Koeduka et al , 2005;Tao et al , 2009;Deng et al , 2012;Yamada et al , 2012;Uji et al , 2016;Ke et al , 2020;Onohata & Gomi, 2020). For example, overexpressing OsWRKY45 andOsC3H12 enhanced Xoo resistance, accumulation of JA, and expression of JA signaling genes (Tao et al , 2009;Deng et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 5-enolpyruvylshikimate-3-phosphate synthase functions as a transcriptional repressor of genes in the phenylpropanoid pathway, in addition to performing its canonical biosynthetic function in the shikimate pathway (Xie et al, 2018 ). In rice ( Oryza sativa ), OsALDH2B1 primarily functions as a mitochondrial aldehyde dehydrogenase regulating male fertility, but it also acts as both a transcriptional repressor and activator, regulating a diverse range of biological processes involving brassinolide, G protein, jasmonic acid, and salicylic acid signaling pathways (Ke et al, 2020 ). Thus, it is possible that a greater number of genes, which were previously considered to encode an enzyme with one function, perform additional roles such as transcriptional activation and are, therefore, involved in multiple metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%